Importance of Routine Histopathological Examination of Gallbladder Specimen in Detecting Incidental Malignancies - Tiwari, Archana; Rai, Ramji; Jain, Surendra Kumar (Journal of Lumbini Medical College, 2017)
Introduction: Gallbladder carcinoma is the most common cancer of biliary tree and the 5thmost common gastrointestinal malignancy. An early diagnosis is essential as this malignancy progresses silently with a late diagnosis and poor prognosis. Epidemiological studies have identified striking geographic and ethnic variation with high occurrence in Southeast Asia, yet low elsewhere in the world. Gallbladder carcinoma, in 15-30% of patients, show no preoperative or intraoperative evidence and are detected only on histopathological examination. They are called as incidental gallbladder cancer (IGBC). The objective of this study was to find out the occurrence of IGBC in cholecystectomy specimens received in our histopathology laboratory and to analyze their clinico-pathological features. Methods: This was a prospective study carried out in the Department of Histopathology, Lumbini Medical College Teaching Hospital during a period of two years from May 2014 to April 2016. The study included 800 cases of cholecystectomized Gall bladder specimens. Result: Ninety seven percent of the specimens (n=776) revealed benign pathology. Malignancy was detected incidentally in 8 cases (1.25%). The mean age of patients with incidental Gall bladder carcinoma was 69 years (SD=4.1) and F:M ratio was 9:1. Out of 10 incidental malignancies, cholelithiasis was found in 8 (80%) cases. Funds was the most common location (n=5, 50%) and focal fragile necrotic area was most common (n=3, 30%) gross morphology. On pathological staging, all the incidentally detected malignancies (n=10) were found to be in surgically respectable stages. Conclusion: IGBC was found in 1.25% of the gallbladder specimen. Detailed gross and histopathological examination of gallbladder specimen is mandatory for every cholecystectomy specimen, even for benign diseases, to detect incidental carcinoma at potentially curable stage. DOI: https://doi.org/10.22502/jlmc.v4i1.76 J. Lumbini. Med. Coll. Vol 4, No 1, Jan-June 2016, Page: 15-19